Pengembangan Sumber Daya Manusia Pada Entrepreneur Muslim untuk Pemberdayaan Ekonomi Lokal di Johar Jakarta Pusat - Dalmeri Dalmeri (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
In the era of regional autonomy the political-economic transformation is still dominated by state and market, while society is in marginal position. Society is often only the object of exploitation of the state and the market. Industrialization developed by the state and the market often forces the middle and small classes to be isolated in their own environment.The potential of natural resources within the middle and small communities is often exploited through access and governance of state and market dominance. When viewed based on the potential that exists, should the governance of the Indonesian economy is based on the industrialization of small and medium-sized society.Experience in the economic crisis of 1998, shows that small and medium industries in the medium and small are relatively able to survive. Compare with large industries that collapsed a lot, unable to survive because the wheels of production driven with machines from debt. The small and medium-sized economy has so far become the main savior of the crisis and the stagnation of economic growth in Indonesia. Efforts to develop local economies through industrialization driven by the urban middle-class society can be an alternative to creating resilience of populist economy, especially in stemming globalization characterized by economic liberalization in various business sectors.This research seeks to analyze some cases, and strategic experience. Especially with regard to Muslim entrepreneurs in the Johar Baru area of Central Jakarta in carrying out various strengthening strategies in local economic development. Entrepreneur Muslim here refers more to the identity of these business actors who are Muslim identity and have a commitment in applying Islamic ethics in running their business and strengthening fellow profession.